Organizational Citizenship Behavior: Peran Kepemimpinan Transformasional dan Keterikatan Kerja - Tiara Dyah Maharani; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to explain the effect of transformational leadership on organizational citizenship behaviour through work engagement. This research is a quantitative study with 43 respondents. This research censused all populations of employees of PT. X. The analysis technique used in this study is the structural equation model partial least square with PLS software version 4.0. The analysis results obtained from this study indicate that transformational leadership and work engagement have a positive and significant effect on organizational citizenship behaviour. Meanwhile, work engagement in this study has yet to be able to mediate the effect of transformational leadership on organizational citizenship behaviour. The leaders need to approach all employees according to the characteristics of each employee so that the delivery of input and directions can be more effective. In addition, it is necessary to have periodic supervision of employees' work so that employees will be more focused when working. Companies also need to involve employees in doing new things outside of work, such as accompanying apprentices or new employees during their orientation period, so employees get used to being open to everyone and accustomed to helping each other even outside their routine jobs.